Global Aerospace Monitoring and Disaster Management - Menshikov, Valery A.; Perminov, Anatoly N.; Urlichich, Yuri M.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2012)
In this book, space systems are situated in the global processes of the 21st century’s information society and the role that space information systems could play in risk management is determined; methods of detecting and forecasting of both natural disasters and technogenic catastrophes and existing global and regional monitoring systems are described; and the IGMASS is introduced with its architecture and design concept and social and economic aspects and estimates of its creation, development, and utilization. Finally, results of the international symposium held in Limassol, Cyprus, in November 2009 in preparation of the IGMASS project’s submission to the United Nations are discussed.
Preface -- I Natural Calamities and its Forecasts -- II Technogenic Emergencies: Can They Be Reliably Predicted? -- III Global Risks and Threats to the Humanity from Outer Space: Prospects of Warning and Parrying -- IV The Conception of the International Global Monitoring Aerospace System (IGMASS) -- V The Role of the Space Exploration in the deal of "Information Field of the Security" formation - a new paradigm of the sustainable development of the Humanity -- Conclusion.
Keywords: Aerospace engineering; Astronautics; Aerospace Technology and Astronautics